Improvement of adhesion performance of mortar-repair interface with inducing crack path into repair - A. Satoh; M. Satoh; K. Yamada (Fracture and Structural Integrity)
The most important performance for repair materials is adhesion to the substrate. The authors experimentally find out that high modulus fine aggregates in repair material enhance strength of it as well as the strength of the interface repaired with it, compared to the ordinary repair without fine aggregates. This paper elaborates the mechanisms for that with fractographic observation and FEM analysis based on the results of experiment. Also the authors discuss the ways for enhancing the strength and ductility of the repaired mortar